2021
DOI: 10.1371/journal.pone.0259942
|View full text |Cite
|
Sign up to set email alerts
|

Plantar fascial fibromatosis and herpes zoster

Abstract: Purpose Infection, chronic pain and depression are considered risk factors for herpes zoster (HZ). However, the correlation between plantar fascial fibromatosis (PFF) and HZ remains unknown. This study investigated HZ risk in patients with PFF. Methods Data was extracted from the Longitudinal Health Insurance Database 2000, which is a subsample of the Taiwan National Health Insurance (NHI) Research Database and contains 1 million NHI beneficiaries. Between 2000 and 2012, patients diagnosed as having PFF were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…The included studies were from Asia ( n = 44), Northern America ( n = 20), Europe ( n = 13) and the Middle East ( n = 3). Most studies were from Taiwan ( n = 30) [ 40 , 41 , 43 , 44 , 50 , 54 , 58 63 , 68 , 76 79 , 81 , 83 85 , 87 , 90 , 96 98 , 100 , 104 , 105 , 115 ] and the US ( n = 19) [ 36 , 37 , 39 , 46 , 47 , 55 , 57 , 64 , 73 , 75 , 80 , 88 , 89 , 99 , 101 , 102 , 106 , 112 , 113 ]. In sum a total study population of 796,796,295 was included, with 10,904,736 HZ cases reported in the included studies.…”
Section: Resultsmentioning
confidence: 99%
“…The included studies were from Asia ( n = 44), Northern America ( n = 20), Europe ( n = 13) and the Middle East ( n = 3). Most studies were from Taiwan ( n = 30) [ 40 , 41 , 43 , 44 , 50 , 54 , 58 63 , 68 , 76 79 , 81 , 83 85 , 87 , 90 , 96 98 , 100 , 104 , 105 , 115 ] and the US ( n = 19) [ 36 , 37 , 39 , 46 , 47 , 55 , 57 , 64 , 73 , 75 , 80 , 88 , 89 , 99 , 101 , 102 , 106 , 112 , 113 ]. In sum a total study population of 796,796,295 was included, with 10,904,736 HZ cases reported in the included studies.…”
Section: Resultsmentioning
confidence: 99%
“…Dupuytren disease is a condition that affects the fascia and causes deformity to the hand, though the causes of itself remain unknown [ 31 ]. A positive association between the risk of herpes zoster and plantar fascial fibromatosis incidence was identified in the literature [ 32 ], but no causal evidence was ever reported. Coeliac disease, sarcoidosis and allergic rhinitis are the consequences of dysregulation of the immune system.…”
Section: Discussionmentioning
confidence: 99%
“…Disease-related stress can trigger the reactivation of VZV. Infectious disease, including those are bacterial [ 8 ] or viral [ 9 ] and that cause chronic musculoskeletal [ 10 12 ] or urogenital [ 13 , 14 ] pain, have been associated with HZ. FLD can have adverse effects on the human body and may induce stress in affected individuals.…”
Section: Introductionmentioning
confidence: 99%